Treatment outcomes among children admitted stabilization centers in Eastern Ethiopia: retrospective study - Ahmed, Jemal Abrahim; Yusuf, Newas; Wilfong, Tara; Tukeni, Kedir Negesso; Berhanu, Hiwot; Roba, Kedir Teji (Frontiers in Public Health, 2023)
Background: There is improved access to Sever Acute Malnutrition management in Ethiopia; however, studies have revealed an alarming rate of defaulters' poor recovery and deaths, emphasizing the importance of researching to identify major causes. As a result, the goal of this research is to identify treatment outcome determinants and associated factors in severely malnourished children aged 6-59 months admitted to public hospitals in Eastern Ethiopia's stabilization centers.Methods: This study used an institutional-based retrospective cohort study design with 712 children aged 6 to 59 months. Data was gathered using a Sever Acute Malnutrition registration logbook and patient charts. Participants were chosen at random from their respective healthcare facilities based on population proportion. Epi-data was entered and analyzed using STATA version 14. To identify associated factors, the Cox proportional hazard Ratio was calculated, and a p-value of 0.05 at the 95% confidence interval was considered statistically significant.Results: This study revealed that only 70.65% (95% CI=67.19,73.88) of the children were cured while 17.84% defaulted from the management and 5.90% died. Children who did not have